DETERMINATION OF SEX USING VARIATIONS IN MINUTIAE DISTRIBUTION IN THUMBPRINTS (Journal of Forensic Medicine & Toxicology, 2022)
The present study is an attempt to explore the distribution of different minutiae in two topological areas of thumbprint and its application to determine sex distinctions. For this purpose, a sample of 100 subjects (50 males and 50 females) ranging in age from 18 years to 25 years was taken from Delhi region in north India. A modified standardized method was adopted to count and classify 20 different types of minutiae. Finding of the study indicates that males had a higher frequency of thumbprint minutiae than females. Ridge endings were the most common feature in both sexes, followed by bifurcation and convergence. In both sexes, the mean values of most minutiae were found to be higher in the outer circle than the inner circle of the thumbprint. A higher chance of female origin is associated with lower frequency of ridge ending (20 for right hand and 31-40 for both right and left hand), convergence (10) and bifurcation (10 and 31- 40 for right hand and 20 for left hand). While a greater frequency of ridge ending (>60 for right hand and >50 for left hand), convergence (>20 for both right and left hand) and bifurcation (>40 for right hand and >30 for left hand) was more likely of male origin. Findings of present study identified sex distinction in the distribution of minutiae with respect to the topological areas on the thumbprint.
Keywords: Sex determination; minutiae; thumbprint; ridge ending; bifurcation